LINEART : international art fair. - Flanders expo, Gent ([s.l.] : Internationale Jaarbeurs van Vlaanderen, 2005)
Abbott, Catalina ; Abe, Yoshiaki ; Acosta, Luis ; Adam, Eric ; Adami ; Aguirre, Philip ; Akkerman, Philip ; Alechinsky, Pierre ; Appel, Karel ; Boël, Delphine ; et al.
Lineart, Flanders Expo, Gent, 2 - 6 december 2005
kunstcatalogus